Economic rent generation through control of the freight element within the supply chain – perspective of VLCC users - Haikal Lutfi Hasbullah (Nanyang Technological University, 2021)
Like all businesses, Very Large Crude Carrier (VLCC) users seek to maximise profits and minimise risks. Profits can be increased by minimising costs, and one of the costs incurred by VLCC users is freight costs. Risks can be mitigated through having a chartering and ownership strategy that is diverse. This paper aims to find an optimal chartering and ownership strategy for VLCC users by using the modern portfolio theory. This paper focuses on the crude oil trade of Arabian Gulf to the Far East using VLCCs, for the period of 2009-2019. Overall, it was discovered that theoretically, the ownership of a 15-year-old vessel in the crude oil trade would bring the highest returns due to its low freight costs. However, after accounting for industry discrimination against older vessels, chartering on the spot market appears to be favourable on most risk levels.